On Ricci solitons in LP-Sasakian manifolds - Shah, Riddhi Jung (BIBECHANA, 2020)
In this paper we study Ricci solitons in Lorentzian para-Sasakian manifolds. It is proved that the Ricci soliton in a (2n+1)-dimensinal LP-Sasakian manifold is shrinking. It is also shown that Ricci solitons in an LP-Sasakian manifold satisfying the derivation conditions R(ξ,X).W2 =0,W2 (ξ,X).W4 =0 and W4 (ξ,X).W2=0 are shrinking but are steady for the condition W2 (ξ,X).S=0. Finally, we give an example of 3-dimensional LP-Sasakian manifold and prove that the Ricci soliton is expanding and shrinking in this manifold. BIBECHANA 17 (2020) 110-116